Non-neoplastic findings at colonoscopy after positive faecal occult blood testing: Data from the English Bowel Cancer Screening Programme. (June 2014) - Bevan, Roisin; Lee, Thomas JW; Nickerson, Claire; Rubin, Greg; Rees, Colin J
Background: The aim of the English Bowel Cancer Screening Programme (BCSP) is to diagnose early colorectal cancer and advanced adenomas. However, other findings are also reported at screening colonoscopy. Small studies demonstrate findings other than cancer or adenomas (non-neoplastic findings (NNF)) in 11–25%. Objectives and setting: Describe the frequency and nature of NNF within the BSCP. Methods: Data were obtained from the BCSP national database for all individuals undergoing colonoscopic investigation after positive faecal occult blood testing between August 2006 and November 2011. Data included demographics, smoking status, neoplastic findings and NNF. Results: 121728 colonoscopies were analysed. ≥1 NNF were found in 26251 cases (21.6%). Diverticular disease (18875 cases) and haemorrhoids (7011) were the most frequently reported. Inflammatory bowel disease (IBD) was reported in 2152 cases. Individuals with a neoplastic diagnosis were less likely to have an NNF than those without (19.8% v 24.4%, p  < 0.001). After adjustment for confounding using multivariable analysis, older age was still associated with a small but statistically significant risk of NNF. Conclusions: The BCSP generates a significant volume of NNF. A small proportion of individuals were found to have inflammatory bowel disease (IBD) - an important diagnosis with implications for long-term management. BCSP participants should be aware that findings other than neoplasia may be detected and the relevance of these findings to that individual is not known. Reporting of NNF varies between colonoscopists, and potential underreporting is a limitation of this study. Further study is required to establish the impact of NNF on primary and secondary care.